2019
DOI: 10.3839/jabc.2019.013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of major ginsenosides in various ginseng samples

Abstract: The contents of major ginsenosides (ginsenosides Rb1, ginsenoside Rc, ginsenoside Rd, ginsenoside Re, ginsenoside Rf, and ginsenoside Rg1) in ginseng cultivated in different areas in Korea, ginseng that underwent different cultivation processes and ages, and ginseng cultivated in different countries were determined using high-performance liquid chromatography equipped with UV/VIS detector. Ginsenoside Rc was the most abundant ginsenoside in all different ginseng samples. The highest total concentration of majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Recent studies have reported that American ginseng exhibits immunomodulatory [ 2 ], antitumour [ 3 ], antioxidative [ 4 ], anti-inflammatory [ 5 ], and antidiabetic [ 6 ] effects, prevents ovarian ageing [ 7 ], and helps in expediting recovery from common cold [ 8 ]. Ginsenosides, as the main secondary metabolites of American ginseng, are the main bioactive components [ 9 , 10 ]. Because of its multiple biological activities, American ginseng has been widely adopted as a fundamental ingredient in functional foods, pharmaceutical products, cosmetics, and nutraceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that American ginseng exhibits immunomodulatory [ 2 ], antitumour [ 3 ], antioxidative [ 4 ], anti-inflammatory [ 5 ], and antidiabetic [ 6 ] effects, prevents ovarian ageing [ 7 ], and helps in expediting recovery from common cold [ 8 ]. Ginsenosides, as the main secondary metabolites of American ginseng, are the main bioactive components [ 9 , 10 ]. Because of its multiple biological activities, American ginseng has been widely adopted as a fundamental ingredient in functional foods, pharmaceutical products, cosmetics, and nutraceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all ginsenosides occur naturally in ginseng. Several factors influence the ginsenoside components of ginseng: cultivation method, harvesting age, and preparation treatment [ 43 – 45 ].…”
Section: Components Of Ginsengmentioning
confidence: 99%
“…For instance, major ginsenosides (Rb1, Rb2, Rc, Rd, Re, and Rg1) can be deglycosylated into minor ginsenosides (F2, Rh2, Rg2, Rg3, and CK) [ 50 ]. Genetics also plays a role in ginsenoside content, as Korean ginseng ( P. ginseng ) has more major ginsenosides than the Chinese ( P. notoginseng ) or American ( P. quinquefolius ) species [ 45 ].…”
Section: Components Of Ginsengmentioning
confidence: 99%